2017
DOI: 10.3847/2041-8213/aa611c
|View full text |Cite
|
Sign up to set email alerts
|

Planetary Nebulae that Cannot Be Explained by Binary Systems

Abstract: We examine the images of hundreds of planetary nebulae (PNe) and find that for about one in six PNe the morphology is too 'messy' to be accounted for by models of stellar binary interaction. We speculate that interacting triple stellar systems shaped these PNe. In this preliminary study we qualitatively classify PNe by one of four categories.(1) PNe that show no need for a tertiary star to account for their morphology. (2) PNe whose structure possesses a pronounced departure from axial-symmetry and/or mirror-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…These are subset of all triple stellar scenarios. The scenario studied in this paper, therefore, accounts for some fraction of the 12 per cents of PNe studied by Bear & Soker (2017). We crudely estimate that the scenario studied in this paper accounts for about 3-5 per cents of all non-spherical PNe.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…These are subset of all triple stellar scenarios. The scenario studied in this paper, therefore, accounts for some fraction of the 12 per cents of PNe studied by Bear & Soker (2017). We crudely estimate that the scenario studied in this paper accounts for about 3-5 per cents of all non-spherical PNe.…”
Section: Discussionmentioning
confidence: 95%
“…However, we can learn from the recent study of Bear & Soker (2017). They present images of 4 typical messy PNe, that they claim are most likely have been shaped by a triple stellar system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HST [N II] image (Figure 10-left) reveals an intricate morphology, with an S-shaped point-symmetric low-ionization structure suggestive of a precessing collimated outflow and a filamentary disk-like structure at the central nebular regions. Bear, & Soker (2017) suggested that M 3-1 maybe shaped by a triple stellar progenitor. It definitely harbors at least a closebinary system with a very short period (Jones et al 2019).…”
Section: -1mentioning
confidence: 99%